Anti-arsenic poisoning denitration catalyst and preparation method thereof
By using the sol-gel method and polymeric alcohol to adjust the pore structure and aluminum coordination in the denitrification catalyst, an anti-arsenic denitrification catalyst was prepared, which solved the problem of catalyst deactivation under high arsenic conditions and significantly improved the denitrification performance.
Patent Information
- Application Number
- CN202411496191.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-11
AI Technical Summary
Existing denitrification catalysts are prone to inactivation and poisoning under high arsenic content, which affects the operating performance of SCR denitrification systems.
The TiO2-Al2O3 composite support was prepared by the sol-gel method, and an anti-arsenic poisoning denitrification catalyst was prepared by adding polymer polymer alcohols such as polyethylene glycol and polypropylene glycol to adjust the pore structure of the support and the coordination state of aluminum.
Under high arsenic loading conditions, the catalyst still maintains excellent denitrification performance, and the denitrification performance was increased by 47.4% and 74.0% at 300℃ and 400℃, respectively, effectively solving the problem of catalysts being prone to poisoning and inactivation.
Smart Images

Figure CN119406400A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flue gas denitration catalysts, and in particular to an arsenic poisoning resistant denitration catalyst and a preparation method thereof. Background Art
[0002] Nitrogen oxides (NOx) are a source of air pollution that can cause serious damage to the environment, such as stratospheric ozone depletion, acid deposition, and photochemical smog, and have a great impact on the human ecological environment. NOx in my country's atmosphere mainly comes from coal burned in coal-fired power plants, steel, glass and other industries. As the main source of nitrogen oxide emissions in my country, it is urgent to reduce nitrogen oxide emissions from coal-fired power plants.
[0003] Selective Catalytic Reduction (SCR) has been proven to be the most effective and widely used denitrification technology, and the catalyst is the core of the overall technology. The performance of the catalyst directly affects the operating efficiency of the SCR denitrification system. In actual operation, the denitrification performance and service life of the catalyst are affected by many factors such as flue gas composition, fly ash erosion and wear, catalyst pore blockage, and chemical poisoning and deactivation. Among them, heavy metal poisoning is one of the important reasons for catalyst deactivation and reduced denitrification performance.
[0004] Among them, arsenic is a heavy metal component commonly found in my country's coal, and its content is mostly concentrated in 0.4-10μg / g. According to the classification method of arsenic content in coal in my country's coal industry standard (MT / T 803-1999), most of my country's coal is secondary arsenic-containing coal (arsenic content> 4-8μg / g), but the arsenic content in the coal mined in southwest my country and Inner Mongolia is relatively high, up to 2000μg / g. When burning high-arsenic coal, the flue gas will contain a large amount of arsenic oxides, causing the SCR catalyst to be poisoned and deactivated, directly affecting the operating performance of the SCR denitrification system. Therefore, avoiding catalyst arsenic poisoning and deactivation is crucial to ensure ultra-low emission operation of high-arsenic coal power generation units.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide an arsenic poisoning resistant denitration catalyst and a preparation method thereof. The arsenic poisoning resistant denitration catalyst still has excellent denitration performance under the condition of high arsenic loading, and effectively solves the problem that the existing denitration catalyst is easily deactivated and poisoned under high arsenic content.
[0007] In a first aspect, the present invention provides a method for preparing an arsenic-poisoning resistant denitrification catalyst, comprising the following steps:
[0008] S1. Add aluminum source and titanium source into an anhydrous ethanol solution, heat and stir to dissolve, and obtain a milky white solution;
[0009] S2, adding a mixed solution of high molecular weight polyol, anhydrous ethanol and water dropwise into the milky white solution to fully hydrolyze and obtain an initial gel;
[0010] S3, the initial gel is dried and calcined for the first time to obtain an Al2O3-TiO2 composite carrier;
[0011] S4, sequentially subjecting the Al2O3-TiO2 composite carrier to impregnation, second drying and second calcination to obtain an arsenic-resistant denitrification catalyst;
[0012] The high molecular weight polyol includes polyethylene glycol and polypropylene glycol. The pore volume, pore diameter and coordination state of aluminum of the Al2O3-TiO2 composite carrier are adjusted by changing the relative molecular weight of the high molecular weight polyol.
[0013] In the preparation method of the arsenic poisoning resistant denitrification catalyst of the present invention, a TiO2-Al2O3 composite carrier is first prepared by a sol-gel method, and a high molecular weight polyol is added as a mesoporous template to control the progress of hydrolysis and polycondensation reactions, thereby preparing a TiO2-Al2O3 composite carrier containing rich intracrystalline mesopores; the obtained Al2O3-TiO2 composite carrier is successively impregnated, dried and calcined to obtain an arsenic poisoning resistant denitrification catalyst.
[0014] Studies have shown that by adjusting the relative molecular weight of the high molecular weight polyol, the pore volume and pore size of the carrier can be effectively adjusted, and the pore structure parameters of the carrier can be further optimized to reduce the blockage of the catalyst pores, thereby improving the capacity to accommodate arsenic oxides. In addition, studies have also found that the high molecular weight polyol introduced in the present invention can also increase the relative proportion of penta-coordinated aluminum in the Al2O3-TiO2 carrier, and the increase in the proportion of penta-coordinated aluminum can effectively promote the uniform dispersion of V and Mo active species on the surface of the Al2O3-TiO2 composite carrier, exposing more active sites, thereby further improving the catalyst's anti-arsenic poisoning performance.
[0015] Specifically, in terms of regulating pore volume and pore size, the polyethylene glycol and polypropylene glycol high molecular weight polyols of the present invention can form a certain molecular chain structure in the solution, and these molecular chains act as templates in the gel formation process, guiding inorganic substances (such as aluminum sources and titanium sources) to deposit around them, thereby forming a composite carrier with a specific pore structure. High molecular weight polyols of different molecular weights have different molecular chain lengths and conformations, so they can produce pores of different sizes and shapes; in addition, the larger the molecular weight of polyethylene glycol and polypropylene glycol, the longer its molecular chain, and the more significant the steric hindrance effect. In the gel formation process, high molecular weight polyethylene glycol or polypropylene glycol can occupy more space, thereby forming a larger pore size and pore volume. On the contrary, low molecular weight polyols tend to form smaller pore size and pore volume. Therefore, the polyethylene glycol and polypropylene glycol high molecular weight polyols of the present invention can regulate the pore volume and pore size of the composite carrier.
[0016] In terms of optimizing pore structure parameters, the addition of polyethylene glycol and polypropylene glycol high molecular weight polyols can also affect the connectivity of the pores. By regulating the molecular weight and addition amount of the high molecular weight polyols, the distribution and connectivity of the pores can be optimized, the pore blockage can be reduced, and the mass transfer efficiency of the catalyst can be improved. At the same time, polyethylene glycol and polypropylene glycol high molecular weight polyols will decompose or volatilize during the heat treatment process and leave a certain surface roughness, which helps to increase the specific surface area and the number of active sites of the catalyst, further improving the performance of the catalyst.
[0017] In terms of regulating the relative proportion of pentacoordinated aluminum, firstly, functional groups such as hydroxyl groups in polyethylene glycol and polypropylene glycol high molecular weight polyols can coordinate with aluminum ions to form stable complexes. This coordination can affect the coordination state of aluminum ions, making them more inclined to form a pentacoordinated aluminum structure. Polyethylene glycol and polypropylene glycol of different molecular weights have different coordination abilities and coordination stabilities, so the relative proportion of pentacoordinated aluminum can be regulated. Secondly, during the heat treatment process, the decomposition and volatilization of polyethylene glycol and polypropylene glycol high molecular weight polyols will promote the rearrangement of aluminum ions and the transformation of the coordination state. Therefore, by regulating parameters such as the heat treatment conditions of hydrolysis and the molecular weight of polyethylene glycol and polypropylene glycol high molecular weight polyols, the proportion and distribution of pentacoordinated aluminum can be further optimized.
[0018] As a preferred embodiment of the present technical solution, the relative molecular mass of the polyethylene glycol used in the present invention is 1000-4000, for example, polyethylene glycol PEG-1000, polyethylene glycol PEG-1500, polyethylene glycol PEG-2000, polyethylene glycol PEG-4000, and the relative molecular mass of the polypropylene glycol is 1000-4000, for example, polypropylene glycol PPG-1000, polypropylene glycol PPG-2000 and polypropylene glycol PPG-4000.
[0019] As a preferred embodiment of the present technical solution, the mass ratio of the oxide Al2O3 corresponding to the aluminum source used in the present invention to the high molecular weight polyol is 1:(0.3-1.5), and preferably 1:0.5.
[0020] As a preferred embodiment of the present technical solution, in step S1, the titanium source includes any one of isopropyl titanate, titanium isopropoxide and tetrabutyl titanate, and is preferably isopropyl titanate; the aluminum source includes any one of aluminum ethanol, aluminum isopropoxide and aluminum sec-butoxide, and is preferably aluminum isopropoxide; and the mass ratio of the oxide Al2O3 and TiO2 corresponding to the aluminum source and the titanium source is (0.3-0.8):1, and is preferably 0.5:1.
[0021] As a preferred embodiment of the present technical solution, in step S1, when heating the titanium source, the aluminum source and the anhydrous ethanol, the temperature is controlled to be 30-70°C and the time is 0.5-3h. The hydrolysis temperature and the hydrolysis time are important factors for controlling the hydrolysis rate of the aluminum source and the titanium source, and at the same time, they are also important factors affecting the proportion of penta-coordinated aluminum in the carrier.
[0022] As a preferred embodiment of the present technical solution, in step S2, the mixed solution of the polymer alcohol of the present invention, anhydrous ethanol and distilled water is preheated and then added dropwise to the milky white solution of step S1 for hydrolysis, and the temperature is controlled at 30-70°C and the time is 2-4h to further control the hydrolysis rate and the polycondensation reaction process.
[0023] As a preferred embodiment of the present technical solution, in step S3, during the first drying, the temperature is controlled to be 50-100°C and the time is 24-48 hours; during the first calcination, the temperature is controlled to be 450-550°C and the time is 3-6 hours. That is, the mesoporous template and other impurities are removed by drying and calcination, the structure and performance of the product are optimized, the crystallization and phase change of the product are promoted, and thus the stability and relative proportion of penta-coordinated aluminum are improved.
[0024] As a preferred embodiment of the present technical solution, in step S4, during the impregnation, the Al2O3-TiO2 composite carrier can be impregnated in a vanadium source and a molybdenum source solution; wherein the vanadium source includes any one or more of ammonium vanadate, ammonium metavanadate and vanadyl oxalate; and the molybdenum source includes any one or more of ammonium heptamolybdate, molybdenum nitrate, molybdenum sulfate and molybdenum trichloride;
[0025] Specifically, in the arsenic poisoning resistant denitration catalyst prepared by the present invention, the mass fraction of V2O5 is 0.8%-2.5%, and the mass fraction of MoO3 is 0.5%-4%.
[0026] As a preferred embodiment of the present technical solution, in step S4, during the second drying, the temperature is controlled to be 80-120°C and the time is 1-4h; during the second roasting, the temperature is controlled to be 400-550°C and the time is 2-8h.
[0027] In the second aspect, the present invention also discloses an arsenic-poisoning-resistant denitration catalyst prepared according to the above preparation method, which should also fall within the protection scope of the present invention.
[0028] The preparation method of the arsenic poisoning resistant denitration catalyst of the present invention has at least the following beneficial effects:
[0029] 1. The present invention adopts the sol-gel method to prepare the TiO2-Al2O3 composite carrier. The addition of high molecular weight polyol during the synthesis process has the following effects: On the one hand, by changing the relative molecular weight of the high molecular weight polyol, the pore volume and pore size of the carrier can be effectively regulated, the pore structure parameters of the carrier can be optimized, and the diffusion rate of arsenic oxide in its pores can be further increased, reducing its influence on the blockage of the catalyst pores; On the other hand, by adding high molecular weight polyol and changing its relative molecular weight, the coordination environment of the aluminum element in the carrier can be effectively regulated, and the relative proportion of penta-coordinated aluminum can be increased. The increase in the content of penta-coordinated aluminum can effectively promote the high dispersion of active species vanadium and molybdenum, expose more reactive sites, improve the reaction activity of the catalyst and improve the anti-arsenic poisoning performance;
[0030] 2. The arsenic poisoning resistant denitration catalyst prepared by the present invention has improved denitration performance by 47.4% and 74.0% respectively compared with the traditional V2O5-MoO3 / TiO2 catalyst in the anti-poisoning performance test (reaction temperature is 300 and 400°C), which effectively solves the problem that the existing denitration catalyst is easily poisoned and deactivated under high arsenic content;
[0031] 3. The preparation method of the arsenic poisoning resistant denitrification catalyst of the present invention has relatively mild reaction conditions, simple process, good repeatability, and can be industrially applied. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is a scanning electron microscope image of the arsenic poisoning resistant denitration catalyst obtained in Example 1 of the present invention;
[0034] Figure 2 This is a scanning electron microscope image of the arsenic poisoning resistant denitration catalyst obtained in Example 2 of the present invention;
[0035] Figure 3 This is a scanning electron microscope image of the arsenic poisoning resistant denitration catalyst obtained in Example 3 of the present invention;
[0036] Figure 4 This is a scanning electron microscope image of the arsenic poisoning resistant denitrification catalyst obtained in Example 4 of the present invention. DETAILED DESCRIPTION
[0037] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0038] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] S11, dissolve 4.00 g of aluminum isopropoxide and 6.33 g of titanium isopropoxide in 42 mL of anhydrous ethanol, and heat in a water bath at 30° C. for 0.5 h to obtain a milky white solution;
[0042] S12, dissolving 0.5 g of polyethylene glycol PEG1000 in a mixed solution of 5 mL of distilled water and 75 mL of anhydrous ethanol, and heating in a water bath at 30°C for 0.5 h; after being completely dissolved, adding the solution dropwise to the milky white solution prepared in S11, and hydrolyzing for 1.5 h to obtain an initial gel;
[0043] S13, placing the obtained initial gel in a drying oven at 80°C for 48 hours, placing the obtained dry gel in a muffle furnace, and calcining it at 450°C for 5 hours in an air atmosphere to obtain an Al2O3-TiO2 composite carrier;
[0044] S14. Ammonium metavanadate and ammonium heptamolybdate are loaded on an Al2O3-TiO2 composite carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the mixture is placed in a drying oven at 80°C for 12 hours. Finally, the obtained sample is placed in a muffle furnace and calcined at 450°C for 4 hours to obtain a V2O5-MoO3 / Al2O3-TiO2 arsenic-resistant denitrification catalyst, wherein the mass fraction of V2O5 is 1.5wt%, and the mass fraction of MoO3 is 3.2wt%.
[0045] Example 2
[0046] S21, dissolve 4.17 g of aluminum sec-butoxide and 5.75 g of titanium isopropoxide in 50 mL of anhydrous ethanol, and heat in a water bath at 35° C. for 1 h to obtain a milky white solution;
[0047] S22, dissolving 0.57 g of polyethylene glycol PEG2000 in a mixed solution of 5 mL of distilled water and 75 mL of anhydrous ethanol, and heating in a water bath at 30° C. for 1 h; after being completely dissolved, adding the solution dropwise to the milky white solution prepared in S21, and hydrolyzing for 2 h to obtain an initial gel;
[0048] S23, placing the obtained initial gel in a drying oven at 95°C for 36 hours, placing the obtained dry gel in a muffle furnace, and calcining it at 500°C for 4 hours in an air atmosphere to obtain an Al2O3-TiO2 composite carrier;
[0049] S24. Ammonium metavanadate and ammonium heptamolybdate are loaded on an Al2O3-TiO2 composite carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the carrier is placed in a drying oven at 80°C for 12 hours. Finally, the obtained sample is placed in a muffle furnace and calcined at 450°C for 4 hours to obtain a V2O5-MoO3 / Al2O3-TiO2 arsenic-resistant denitrification catalyst, wherein the mass fraction of V2O5 is 2.0wt%, and the mass fraction of MoO3 is 3.0wt%.
[0050] Example 3
[0051] S31. Dissolve 4.72 g of aluminum ethoxide and 5.05 g of titanium isopropoxide in 45 mL of anhydrous ethanol, and heat in a water bath at 40° C. for 1.5 h to obtain a milky white solution.
[0052] S32, dissolving 0.58 g of polyethylene glycol PEG4000 in a mixed solution of 5 mL of distilled water and 90 mL of anhydrous ethanol, and heating in a water bath at 38° C. for 2 h; after being completely dissolved, adding the solution dropwise to the milky white solution prepared in S31, and hydrolyzing for 2 h to obtain an initial gel;
[0053] S33, placing the obtained initial gel in a drying oven at 100°C for 48 hours, placing the obtained dry gel in a muffle furnace, and calcining it at 550°C for 3 hours in an air atmosphere to obtain an Al2O3-TiO2 composite carrier;
[0054] S34. Ammonium metavanadate and ammonium heptamolybdate are loaded on an Al2O3-TiO2 carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the carrier is placed in a drying oven at 80°C for 12 hours. Finally, the obtained sample is placed in a muffle furnace and calcined at 550°C for 3 hours to obtain a V2O5-MoO3 / Al2O3-TiO2 arsenic-resistant denitrification catalyst, wherein the mass fraction of V2O5 is 1.5wt%, and the mass fraction of MoO3 is 2.8wt%.
[0055] Example 4
[0056] S41, dissolve 4.72 g of aluminum isopropoxide and 7.15 g of titanium isopropoxide in 40 mL of anhydrous ethanol, and heat in a water bath at 40° C. for 1.5 h to obtain a milky white solution;
[0057] S42, dissolving 0.58 g of polyethylene glycol PEG1500 in a mixed solution of 7 mL of distilled water and 95 mL of anhydrous ethanol, and heating in a water bath at 40° C. for 1.5 h; after being completely dissolved, adding the solution dropwise to the milky white solution prepared in S42, and hydrolyzing for 2 h to obtain an initial gel;
[0058] S43, placing the obtained initial gel in a drying oven at 95°C for 48 hours, placing the obtained dry gel in a muffle furnace, and calcining it at 500°C for 3 hours in an air atmosphere to obtain an Al2O3-TiO2 composite carrier;
[0059] S44. Ammonium metavanadate and ammonium heptamolybdate are loaded on an Al2O3-TiO2 composite carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the mixture is placed in a drying oven at 80°C for 12 hours. Finally, the obtained sample is placed in a muffle furnace and calcined at 550°C for 3 hours to obtain a V2O5-MoO3 / Al2O3-TiO2 arsenic-resistant denitrification catalyst, wherein the mass fraction of V2O5 is 1.5wt%, and the mass fraction of MoO3 is 2.5wt%.
[0060] Example 5
[0061] S51, dissolve 3.95 g of aluminum sec-butoxide and 6.50 g of titanium isopropoxide in 48 mL of anhydrous ethanol, and heat in a water bath at 35° C. for 2.5 h to obtain a milky white solution;
[0062] S52, dissolving 0.45 g of polypropylene glycol PPG1000 in a mixed solution of 5 mL of distilled water and 95 mL of anhydrous ethanol, and heating in a water bath at 35° C. for 1.5 h; after being completely dissolved, adding the solution dropwise to the milky white solution prepared in S51, and hydrolyzing for 2 h to obtain an initial gel;
[0063] S53, placing the obtained initial gel in a drying oven at 80°C for 36 hours, placing the obtained dry gel in a muffle furnace, and calcining it at 500°C for 3 hours in an air atmosphere to obtain an Al2O3-TiO2 composite carrier;
[0064] S54. Ammonium metavanadate and ammonium heptamolybdate are loaded on an Al2O3-TiO2 composite carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the mixture is placed in a drying oven at 80°C for 12 hours. Finally, the obtained sample is placed in a muffle furnace and calcined at 500°C for 3 hours to obtain a V2O5-MoO3 / Al2O3-TiO2 arsenic-resistant denitrification catalyst, wherein the mass fraction of V2O5 is 1.7wt%, and the mass fraction of MoO3 is 2.8wt%.
[0065] Example 6
[0066] S61, dissolve 4.25 g of aluminum sec-butoxide and 6.50 g of titanium isopropoxide in 45 mL of anhydrous ethanol, and heat in a water bath at 35° C. for 2.5 h to obtain a milky white solution;
[0067] S62, dissolving 0.45 g of polypropylene glycol PPG2000 in a mixed solution of 5 mL of distilled water and 95 mL of anhydrous ethanol, and heating in a water bath at 35° C. for 1.5 h; after being completely dissolved, adding the solution dropwise to the milky white solution prepared in S26, and hydrolyzing for 2 h to obtain an initial gel;
[0068] S63, placing the obtained initial gel in a drying oven at 70°C for 48 hours, placing the obtained dry gel in a muffle furnace, and calcining it at 500°C for 3 hours in an air atmosphere to obtain an Al2O3-TiO2 composite carrier;
[0069] S64. Ammonium metavanadate and ammonium heptamolybdate are loaded on an Al2O3-TiO2 composite carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the mixture is placed in a 90°C drying oven for 16 hours. Finally, the obtained sample is placed in a muffle furnace and calcined at 550°C for 3 hours to obtain a V2O5-MoO3 / Al2O3-TiO2 arsenic-resistant denitrification catalyst, wherein the mass fraction of V2O5 is 1.8wt%, and the mass fraction of MoO3 is 2.8wt%.
[0070] Example 7
[0071] S71, dissolve 4.25 g of aluminum sec-butoxide and 6.00 g of titanium isopropoxide in 45 mL of anhydrous ethanol, and heat in a water bath at 35° C. for 2.5 h to obtain a milky white solution;
[0072] S72, dissolving 0.45 g of polypropylene glycol PPG4000 in a mixed solution of 5 mL of distilled water and 95 mL of anhydrous ethanol, and heating in a water bath at 40° C. for 1.5 h; after being completely dissolved, adding the solution dropwise to the milky white solution prepared in S26, and hydrolyzing for 2 h to obtain an initial gel;
[0073] S73, placing the obtained initial gel in a drying oven at 85°C for 48 hours, placing the obtained dry gel in a muffle furnace, and calcining it at 550°C for 3 hours in an air atmosphere to obtain an Al2O3-TiO2 composite carrier;
[0074] S74. Ammonium metavanadate and ammonium heptamolybdate are loaded on an Al2O3-TiO2 composite carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the mixture is placed in a 90°C drying oven for 16 hours. Finally, the obtained sample is placed in a muffle furnace and calcined at 550°C for 3 hours to obtain a V2O5-MoO3 / Al2O3-TiO2 arsenic-resistant denitrification catalyst, wherein the mass fraction of V2O5 is 2.0wt%, and the mass fraction of MoO3 is 4.0wt%.
[0075] Comparative Example 1
[0076] This comparative example is substantially the same as Example 3, except that no high molecular weight polyol is added during the synthesis process.
[0077] Comparative Example 2
[0078] This control example is basically the same as Example 3, except that PEG2000 is used to replace PEG4000 in Example 3.
[0079] Comparative Example 3
[0080] This control example is basically the same as Example 3, except that PEG1500 is used to replace PEG4000 in Example 3.
[0081] Comparative Example 4
[0082] This control example is basically the same as Example 3, except that PEG1000 is used to replace PEG4000 in Example 3.
[0083] Comparative Example 5
[0084] This control example is basically the same as Example 7, except that PEG2000 is used to replace PPG4000 in Example 7.
[0085] Comparative Example 6
[0086] This control example is basically the same as Example 7, except that PEG1000 is used to replace PPG4000 in Example 7.
[0087] Comparative Example 7
[0088] This control example is basically the same as Example 3, except that polypropylene alcohol with a relative molecular weight of 400 is used to replace PEG1000 in Example 3.
[0089] Comparative Example 8
[0090] This control example is basically the same as Example 3, except that polypropylene alcohol with a relative molecular weight of 700 is used to replace PE4000 in Example 3.
[0091] Comparative Example 9
[0092] This comparative example is substantially the same as Example 3, except that polypropylene alcohol with a relative molecular weight of 2000 is used to replace PEG4000 in Example 3.
[0093] Comparative Example 10
[0094] This control example is basically the same as Example 7, except that polyvinyl alcohol with a relative molecular weight of 25,000 is used to replace PPG1000 in Example 7.
[0095] Comparative Example 11
[0096] This control example is basically the same as Example 7, except that polyvinyl alcohol with a relative molecular weight of 30,000 is used instead of PPG1000 in Example 7.
[0097] Comparative Example 12
[0098] This control example is basically the same as Example 7, except that polyvinyl alcohol with a relative molecular weight of 35,000 is used to replace PPG1000 in Example 7.
[0099] Figure 1-4 The scanning electron microscope images of the arsenic-poisoning-resistant denitration catalysts prepared in Examples 1-4 of the present invention show that the Al2O3-TiO2 composite carriers present different nanosheet-like loose stacking structures.
[0100] The present invention further characterized the nitrogen adsorption-desorption of the Al2O3-TiO2 composite carriers obtained in Example 3, Example 7 and Comparative Examples 1-12. The results are shown in Table 1.
[0101] Table 1 Nitrogen adsorption-desorption characterization test results of Example 3 and Comparative Examples 1-4
[0102]
[0103] Table 2 Nitrogen adsorption-desorption characterization test results of Example 7 and Comparative Examples 5-6
[0104]
[0105] Table 3 Comparative Examples 7-9 Nitrogen adsorption-desorption characterization test results
[0106]
[0107] Table 4 Comparative Examples 10-12 Nitrogen adsorption-desorption characterization test results
[0108]
[0109] It can be seen from Tables 1-4 that the addition of polyethylene glycol and polypropylene glycol with different molecular weights can significantly improve the pore structure characteristics of the Al2O3-TiO2 composite carrier. Moreover, with the increase of the relative molecular weight of the high molecular weight polyol, the pore volume and pore diameter of the composite carrier also increase. In particular, the pore volume of the composite carrier prepared by adding polyethylene glycol PEG-4000 can reach 1.15mL / g and the pore diameter can reach 20.7nm; the pore volume of the composite carrier prepared by adding polypropylene glycol PEG-4000 can reach 0.98mL / g and the pore diameter can reach 18.4nm.
[0110] Although different molecular weights of polyols were added to control examples 7-12, the pore structure characteristics of the obtained Al2O3-TiO2 composite carrier did not increase or decrease regularly. The reasons are as follows: the molecular weight of the polyol is relatively small, and it is not easy to play a structural guiding role in the hydrolysis process of the titanium source and the aluminum source, and the steric hindrance is small; the molecular weight of the polyol is too large, and it is easy to agglomerate in the synthesis system, and it is easy to separate into two phases with the gel product of the hydrolysis of the titanium source and the aluminum source, and the template filling effect is not obvious. This shows that the high molecular weight polyol used to adjust the pore structure characteristics of the composite carrier of the present invention is not a polyol of any different molecular weight.
[0111] In addition, the present invention also uses aluminum nuclear magnetic resonance to test the coordination environment and proportion of aluminum elements in the arsenic-resistant denitrification catalyst composite carriers prepared in Example 3, Example 7 and Comparative Examples 1-12. The test results are shown in Tables 5-8.
[0112] Table 5 Coordination environment and proportion of aluminum in the composite carrier of Example 3 and Comparative Examples 1-4
[0113]
[0114] Table 6 Coordination environment and proportion of aluminum in the composite carrier of Example 7 and Comparative Examples 5-6
[0115]
[0116] Table 7 Comparative Examples 7-9 Coordination environment and proportion of aluminum in the composite carrier
[0117]
[0118] Table 8 Coordination environment and proportion of aluminum in the composite carrier of Comparative Examples 10-12
[0119]
[0120] It can be seen from Tables 5-8 that the addition of high molecular weight polyols of different molecular weights of the present invention not only affects the pore structure characteristics of the composite support, but also affects the coordination environment of aluminum in the composite support; with the increase of the molecular weight of polyethylene glycol or polypropylene glycol, the relative proportion of penta-coordinated aluminum in the composite support shows an increasing trend. Studies have shown that an increase in the proportion of penta-coordinated aluminum can improve the dispersibility of active species, which is conducive to exposing more active sites to improve the denitration reaction performance of the catalyst.
[0121] Although different molecular weights of polyols were added to the control examples 7-12, the coordination environment of aluminum in the obtained Al2O3-TiO2 composite carrier did not increase or decrease regularly. This may be because there is a large repulsion between polypropylene alcohol and polyvinyl alcohol and the hydrolyzed products of the titanium source and the aluminum source, and the interaction between the two is weak, resulting in severe separation of the two phases. This further illustrates that the high molecular weight polyol used to adjust the coordination environment of aluminum in the composite carrier of the present invention is not a polyol of any different molecular weight.
[0122] The present invention further uses the above sample as a denitration catalyst to explore its catalytic performance, and the specific experimental method is as follows:
[0123] Arsenic poisoning of denitrification catalyst adopts simulated poisoning method, as follows:
[0124] The denitration catalyst was passed through a 20-40 mesh sieve, and the catalyst powder was weighed and placed in a tubular furnace. A certain amount of As2O3 was placed at the front end of the denitration catalyst. N2 containing 3 vol% H2O was introduced into the tubular furnace and heated to 350°C. As2O3 vapor will be loaded on the denitration catalyst as the gas flows. Subsequently, the denitration catalyst was treated at 370°C for 10 hours in an N2 atmosphere containing 3 vol% O2 to obtain a denitration catalyst simulating arsenic poisoning.
[0125] Furthermore, the denitration performance test of the denitration catalyst after arsenic poisoning was carried out in a normal pressure micro fixed bed reactor, the denitration catalyst loading was 0.3g, and a mixed gas of NO, NH3, O2 and N2 was used to simulate industrial flue gas, wherein the volume fractions of NO, NH3 and O2 were 0.05%, 0.05% and 5% respectively, N2 was used as a balance gas, and the mixed gas flow rate was 1L / min. A GA-21plus flue gas analyzer (Madur, Austria) was used to analyze the volume fractions of NO and NO2 in the mixed gas after the reaction, and the denitration efficiency ηNO (%) was calculated according to the following formula. The denitration efficiency of the denitration catalyst at different temperatures was obtained by the calculation of this formula, and the results are shown in Tables 9-12 for details.
[0126] ηNO(%)=([NO] in -[NO] out -[NO2] out ) / [NO] in ×100%
[0127] Table 9 Denitration efficiency of denitration catalysts in Example 3 and Comparative Examples 1-4
[0128]
[0129] Table 10 Denitration efficiency of denitration catalysts in Example 7 and Comparative Examples 5-6
[0130]
[0131] Table 11 Denitration efficiency of denitration catalysts in comparative examples 7-9
[0132]
[0133]
[0134] Table 12 Denitration efficiency of denitration catalysts in comparative examples 10-12
[0135]
[0136] As shown in Tables 9-12, after adding high molecular weight polyol to the composite carrier prepared in Example 3, Example 7 and Comparative Examples 2-6 to load active components of vanadium and molybdenum, the denitration activity of the simulated catalyst under arsenic-containing conditions is significantly improved compared with the fresh catalyst, and the NO conversion rate can be further increased from 60.1% at 300°C to 88.6%; after increasing the temperature to 400°C, it still has a high denitration activity of up to 87.1%. In particular, the catalytic activity of the catalyst prepared by adding polyethylene glycol PEG4000 and polypropylene glycol PPG400 is least affected. It further illustrates that the addition of polyethylene glycol and polypropylene glycol high molecular weight alcohols of different molecular weights of the present invention can significantly improve the anti-arsenic poisoning performance of the catalyst.
[0137] Although the use of polyvinyl alcohol or polypropylene alcohol in Comparative Examples 7-12 can improve the arsenic poisoning resistance of the catalyst to a certain extent, the arsenic poisoning of the catalyst is more serious when the reaction temperature is high.
[0138] In summary, the arsenic-poisoning resistant denitration catalyst prepared by the present invention still has excellent denitration performance under the condition of high arsenic loading, which effectively solves the problem that the existing denitration catalyst is easily deactivated and poisoned under high arsenic content.
[0139] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an arsenic-resistant denitrification catalyst, characterized in that: The following steps are involved: S1. Add aluminum source and titanium source into an anhydrous ethanol solution, heat and stir to dissolve, and obtain a milky white solution; S2, adding a mixed solution of high molecular weight polyol, anhydrous ethanol and water dropwise into the milky white solution to fully hydrolyze and obtain an initial gel; S3, the initial gel is dried and calcined for the first time to obtain an Al2O3-TiO2 composite carrier; S4, sequentially subjecting the Al2O3-TiO2 composite carrier to impregnation, second drying and second calcination to obtain an arsenic-resistant denitrification catalyst; The high molecular weight polyol includes polyethylene glycol and polypropylene glycol. The pore volume, pore diameter and coordination state of aluminum of the Al2O3-TiO2 composite carrier are adjusted by changing the relative molecular weight of the high molecular weight polyol.
2. The preparation method according to claim 1, characterized in that: The relative molecular mass of the polyethylene glycol is 1000-4000, and the relative molecular mass of the polypropylene glycol is 1000-4000.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the oxide Al2O3 corresponding to the aluminum source to the high molecular weight polyol is 1:(0.3-1.5).
4. The preparation method according to claim 1, characterized in that: In step S1, the titanium source includes any one of isopropyl titanate, titanium isopropoxide and tetrabutyl titanate; The aluminum source includes any one of aluminum ethoxide, aluminum isopropoxide and aluminum sec-butoxide; The mass ratio of the oxides Al2O3 and TiO2 corresponding to the aluminum source and the titanium source is (0.3-0.8):
1.
5. The preparation method according to claim 1, characterized in that: In step S1, during the heating and stirring, the temperature is controlled to be 30-70°C and the time is 0.5-3h.
6. The preparation method according to claim 1, characterized in that: In step S2, during the hydrolysis, the temperature is controlled to be 30-70° C. and the time is 2-4 hours.
7. The preparation method according to claim 1, characterized in that: In step S3, during the first drying, the temperature is controlled to be 50-100° C. and the time is 24-48 hours; During the first calcination, the temperature is controlled at 450-550° C. and the time is 3-6 hours.
8. The preparation method according to claim 1, characterized in that: In step S4, during the impregnation, the Al2O3-TiO2 composite support is impregnated in a vanadium source and a molybdenum source solution; The vanadium source includes any one or more of ammonium vanadate, ammonium metavanadate and vanadyl oxalate; The molybdenum source includes any one or more of ammonium heptamolybdate, molybdenum nitrate, molybdenum sulfate and molybdenum trichloride; In the arsenic-poisoning resistant denitration catalyst, the mass fraction of V2O5 is 0.8%-2.5%, and the mass fraction of MoO3 is 0.5%-4%.
9. The preparation method according to claim 1, characterized in that: In step S4, during the second drying, the temperature is controlled to be 80-120° C. and the time is 1-4 hours; During the second calcination, the temperature is controlled at 400-550° C. and the time is 2-8 hours.
10. An arsenic-poisoning resistant denitrification catalyst, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.